Testing the Philips Curve Model Based on Financial Technology and Macroprudential Policy in ASEAN Countries with the Highest Unemployment Rate - Syahfia, Nurul; Nazliana Nasution, Lia; Rusiadi, Rusiadi (Lafadz Jaya Publisher, 2024)
Financial technology integration can influence unemployment rates in various ways, such as expanding access to the labor market through online platforms, creating new jobs within the financial technology sector itself, or increasing labor market efficiency through technologies such as job matching platforms. Macroprudential policy refers to the steps taken by financial authorities to manage systemic risks in the financial sector. In the context of the Phillips curve, these policies can have a direct or indirect effect on the unemployment rate through their influence on financial system stability and economic growth. In relation to ASEAN countries with the highest unemployment rates, testing this model will pay attention to structural, demographic and economic differences between these countries. These factors will influence how financial technology and macroprudential policy interact with the unemployment rate in each country. The results of this test provide valuable insights for policymakers in ASEAN countries with high unemployment rates. They can use this information to design more effective policies in promoting economic growth and reducing unemployment rates through the appropriate application of financial technology and macroprudential policies.